(untitled) (Research, Society and Development, 2022)
The global neurocognitive manifestations related to HIV infection are widely known. Several research groups around the world have studied the presence of HIV variants in different biological compartments, with discordant HIV-RNA levels between plasma and tissues. The aim of the present study was to investigate the viral escape of HIV in a patient with neurodegenerative manifestations, in whom no reason aside from HIV-related activity was found, despite effective antiretroviral therapy (ART). This is a descriptive Case Report, based on retrospective information obtained by medical record review, patient interviews, laboratory test results, and reports filed at the Infectious Diseases Service of the São José Hospital for Infectious Diseases (HSJ), in Fortaleza, Ceará, Brazil. The obtained data indicate that HIV compartmentalization in the CNS can be facilitated by viral variants of a phenotype that enables effective replication in cells such as microglia or monocytes, especially when considering the limited penetration of ART through the blood-brain barrier, favoring the persistence of replication, increased genetic diversity, and the sustainment of viral reservoirs.